HUBUNGAN KECERDASAN EMOSIONAL DAN TINGKAT KONSENTRASI TERHADAP KETEPATAN SHOOTING DI KIE FUTSAL CLUB U-20 CILACAP TAHUN 2021 - Permadi, Rachmat (Universitas Negeri Semarang, 2021)
Emotional intelligence and the level of concentration are aspects related to mental. The formulation ofthe problem is Is there a relationship between emotional intelligence and the level of concentration onthe accuracy of shooting results?. The purpose of this study was to determine the relationship betweenemotional intelligence and the level of concentration on the accuracy of shooting results on the KIEFutsal Club U-20 futsal team in Cilacap Regency.The research uses quantitative methods. The dataanalysis technique uses product moment correlation analysis. Correlation test data obtained throughPearson product moment by showing the hypothesis 1) There is no relationship between emotionalintelligence and shooting accuracy, 2) there is a relationship between concentration level and shootingaccuracy, 3) there is a relationship between emotional intelligence and concentration level with shootingaccuracy. The conclusion of the study is that there is a relationship between emotional intelligence andthe level of concentration on shooting accuracy. Research advice is for players to always maintainemotional intelligence and concentration so that when shooting at goal they have good results. Coachesare expected to always pay attention to the psychological factors of players both during training andmatches.